The Influence of Compensation, Workload, Work Environment, and Leadership on Employee Work Productivity at PT Surya Madistrindo - Dani Rizki Ariyanto; Fatwa Zuhaena; Herwiek Diyah Lestari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Employee productivity is a crucial factor in achieving organizational effectiveness and competitiveness and is influenced by various organizational and managerial factors. This study aims to analyze the effects of compensation, workload, work environment, and leadership on the work productivity of employees at PT Surya Madistrindo. This research employed a quantitative approach with a population of 90 employees of PT Surya Madistrindo. A total of 79 respondents were selected using the proportionate stratified random sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS Statistics 26. The results indicate that compensation, work environment, and leadership have a positive and significant effect on employee work productivity, while workload has a negative and significant effect on employee work productivity. Simultaneously, all independent variables significantly influence employee work productivity. These four independent variables explain 52.4% of the variation in employee productivity, while the remaining 47.6% is influenced by other factors outside the scope of this study. The findings suggest that improving compensation systems, creating a supportive work environment, strengthening effective leadership, and managing employee workload appropriately are essential for enhancing employee productivity. Therefore, the management of PT Surya Madistrindo should implement integrated human resource management strategies that focus on employee welfare, effective leadership, workload optimization, and the development of a conducive work environment to improve organizational performance. The findings of this study are expected to serve as a valuable reference for company management and future researchers in developing strategies to enhance employee productivity.